O caso Justa Trama: contexturas entre a economia solidária e as estratégias orientadas para a sustentabilidade no processo de Life Cycle Design (ModaPalavra e-periódico, 2014)
Wide possibilities for the role of design has been concentrated on the task of mediating material production and its relations of production and consumption and, between this varied perspectives, its the challenge of assisting the development of effective and lasting benefits for individuals and social groups in their territories. From this approach, design-oriented strategies to promote social, environmental and economic improvements have been gathered to initiatives of production and consumption, based on the principles of solidarity Economy (SE). Thus, the implementation of these strategies has emerged as one of the key factors in the search for feasible alternatives for expanding the conditions of local development. According to these assumptions, this article examines the case of the association Justa Trama, because this enterprise has its actions based on the “connections” of solidarity economy in search of social, environmental and economic benefits for its members and for society as a whole. As results observed during the examination of the case, it was found that Justa Trama brings together diverse strategies oriented to social, environmental and economic sustainability, as these strategies are already inserted intrinsecaly in the Life Cycle Design (LCD) of products developed by the association. From an organizational model based on values of solidarity, Justa Trama has succeeded in its purpose of providing autonomy to the cooperative members in the different stages of production, while it manages to maintain an alignment with their core foundations also in the stages of distribution and consumption.
Keywords: strategies on design and sustainability; life Cycle Design; solidarity economy; popular cooperatives